Enhanced passive safety surveillance of the quadrivalent inactivated split-virion influenza vaccine (IIV4) in Finland during the 2019/20 influenza season - Anne-Laure Chabanon; Sophie Wague; Annick Moureau; Markku Nissila; Laurence Serradell (BMC, 2021)
Abstract Background and aims The Enhanced Passive Safety Surveillance is a requirement of the European Medicines Agency (EMA) for seasonal influenza vaccines, aiming to rapidly detect any significant change in frequency or severity of expected reactogenicity or allergic events prior to widespread use of a vaccine in any particular year. The aim of this surveillance was to assess the quadrivalent inactivated split-virion influenza vaccine (IIV4) during routine immunization in Finland, as per the national immunization program for 2019/20. The primary objective was to investigate the suspected adverse drug reactions (ADR) occurring within 7 days following vaccination. Methods Passive surveillance of individuals vaccinated with IIV4 was conducted within the first 4 to 6 weeks of the influenza season in Finland. Potential ADRs were reported via phone or posted adverse event forms. The vaccinee reporting rate and ADR reporting rate were calculated and compared with the known or expected safety data in order to identify any change which was clinically significant. Results Data were collected from 939 individuals, with 56 reports received for 163 suspected ADRs. Of these, 38 individuals reported 117 suspected ADRs within 7 days following vaccination, corresponding to an ADR reporting rate of 12.46% (95% CI: 10.41, 14.74%); vaccination-site pain, vaccination-site reaction, and pyrexia were the most frequently reported ADRs. The 18-to-65 years of age category had an ADR reporting rate of 12.56%, the over-65 years of age category had an ADR reporting rate of 16.22%, and no ADRs were reported for individuals aged 6 months to 18 years. No serious suspected ADRs were reported at any time post-vaccination, and the ADR rates were comparable to those reported for IIV4 in the 2018/19 seasonal assessment. The frequency of suspected ADRs was generally aligned with those reported in the Summary of Product Characteristics (SmPC), with the exception of asthenia, somnolence, and erythema, which were slightly higher. No reporting pattern by type, frequency, or severity was identified for the suspected ADRs. Conclusions No clinically significant changes in what is known or expected for IIV4 was reported for the 2019/20 season, which supports the overall safety profile.